LEGAL AWARENESS OF YOUNGSTERS AS SUBJECT OF PEDAGOGICAL RESEARCH - Liliya Riabovol (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article gives an overview of approaches by ukrainian scientists on legal awareness as the effective rate of training of law students of secondary schools and graduates not majoring in law. The results of the study demonstrate that native scholars consider legal education as a combination of systemic knowledge about law and legislation, skills to use it in familiar and non-familiar situations, to choose appropriate behavior and be ruled by the principles of law, respect for human rights, etc., however, they integrate these elements in different structural components. The paper defines legal awareness as a set of cognitive (legal knowledge, abilities and skills to obtain and use it, to think critically and logically), action-operational (the ability to use legal knowledge to carry out practical tasks, solve problems in the legal field; implement the provisions of law for the effective interaction between the subjects of study and social life), value-motivational or axiological (legal values, values and emotional attitude to the state and legal phenomena, motivation of lawful behavior) components.